The effects of a corticotomy on space closure by molar protraction using TSADs in patients with missing mandibular first molars. (2nd August 2021) - Park, Jae Hyun; Kim, Kyung Wook; Lee, Nam‐Ki; Ku, Ja Hyeong; Kim, Jaehyun; Kook, Yoon‐Ah; Chou, Alex Hung Kuo; Kim, Yoonji
Abstract: Introduction: The purpose of this study was to evaluate the effects of a triangular‐shaped corticotomy on the protraction of second and third molars in patients with missing mandibular first molars. Subjects and Methods: The corticotomy and non‐corticotomy groups consisted of sixteen first molars in fifteen patients (28.6 ± 9.4 years) and nineteen first molars in fifteen patients (26.6 ± 8.4 years), respectively. A triangular‐shaped corticotomy was performed between the second premolar and molar. Temporary skeletal anchorage devices (TSADs) were placed between the first and second premolars in both groups. Mandibular dentition variables were measured on the pre and post‐treatment panoramic radiographs and lateral cephalograms. Analysis of covariance was performed. Results: The corticotomy group exhibited 2.8 mm more inter‐radicular correction between the second molar to second premolar roots ( P  < .001) and 1.6 mm more inter‐radicular distance correction between the third molar to second premolar roots compared to the non‐corticotomy group ( P  < .01). The corticotomy group required 5.5 months less treatment time for space closure ( P  < .05), but the total treatment time was the same for both groups. Conclusions: The inter‐radicular distance between the mandibular second premolar and molar and treatment times for space closure was significantly reduced in the corticotomy group.